New Separation Techniques for Output-Only Modal Analysis - Jérôme Antoni; Luigi Garibaldi; Stefano Marchesiello; Menad Sidhamed (Shock and Vibration)
The paper is devoted to the problem of discriminating between operational and natural modes of structures excited by generic inputs. This case often occurs when the system under analysis holds rotating parts and is contemporary excited by ambient noise; in this case the output-only techniques may fail being easily trapped in a misinterpretation of the system eigenvalues. A survey of the methods available in literature is given, together with the explanation of their failures. To solve this problem, two new techniques are introduced and their capabilities are checked with numerical and experimental data from a paper machine.